Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙÙŠ Ù‚ØµÙŠØ¯Ø© Ø§Ù„Ø¨Ø±Ø¯Ø© Ù„Ù„Ø¥Ù…Ø§Ù… Ø§Ù„Ø¨ÙˆØµÙŠØ±ÙŠ (Ø¯Ø±Ø§Ø³Ø© Ø£Ø¯Ø¨ÙŠØ©) - Mustafa, Raden Suparman (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2017)
Qasidah Burdah Imam al-Bushiri consists of 160 stanzas, which contains about the "Advice and Warnings". As greedy lust, praise to the Prophet, the Prophet's birth, glory of the Qur'an, Isra 'Mi'raj, and jihad of the Prophet Muhammad. Objectives to be achieved by the authors of this research is to know the kinds of goals and values ​​of Islam contained in Qasidah Burdah Imam al-Bushiri. This research is a qualitative research, while the method used is descriptive method (to give an overview and explanation of Qasidah Burdah) as well as the method of analysis (as a tool to examine more deeply about Qasidah Burdah in this study). Conclusion The results of this research are: 1) there are two objectives (Aghrodh) is in Qasidah Burdah Imam al-Bushiri, namely - Praise (Hymn), - Ghazl (Flirt). such as the temple of 1-2, 29-32, 59, 85-86, 102-105, 114-117. 2) Then there are three kinds of Islamic values ​​in Qasidah Burdah Imam al-Bushiri, namely: 1). Value of thought as in stanzas 8, 100-101, 133-134. 2). Ethics / ahlak as the temple of 29-32, 54-58, 112-113. 3). Values ​​such as the temple deity to 150-155.